Aristotle’s Theory of Practical Cognition - Ando, Takatsura. author. aut Link
XIV, 282 p.
Keywords: I have much pleasure in writing a preface to Mr. Takatura Ando's book on Aristotle. Apart from his intrinsic importance, as one of the three or four greatest of all philosophers, Aristotle is important on having given for many centuries the greatest influence in moulding the thought of European countries. The language difficulty has no doubt prevented him from exercising very much influence on Japanese thought, and I welcome very warmly to hear that Mr. Ando is about to have his book printed in Japan. I hope it will be widely circulated, as it must certain ly deserve that. W. D. Ross AUTHOR'S FOREWORD In publishing this book, I cannot prohibit myself of reminding the days and nights when it was written. In that era of worldwide madness, Aristotle's philosophy was the only refuge wherein my depressed mind could come to life. It was written bit by bit under all desperate circum stances throughout the war time. My heart was set on the completion of this work while the fate allowed me to live. It was nearly carried out by the end of the war. Having no hope of survival, I buried my manu script in the earth, without however any expectance of a better lot for it.